Fluorine-18 patents (2009–2015). Part 2: new radiochemistry. (September 2016) - Mossine, Andrew V; Thompson, Stephen; Brooks, Allen F; Sowa, Alexandra R; Miller, Jason M; Scott, Peter JH
Fluorine-18 ( 18 F) is one of the most common positron-emitting radionuclides used in the synthesis of positron emission tomography radiotracers due to its ready availability, convenient half-life and outstanding imaging properties. In Part 1 of this review, we presented the first analysis of patents issued for novel radiotracers labeled with fluorine-18. In Part 2, we follow-up with a focus on patents issued for new radiochemistry methodology using fluorine-18 issued between January 2009 and December 2015.